Preliminary phases of the HIDRALERTA system: Assessment of the flood levels at S. João da Caparica beach, Portugal - Raposeiro, P. (2013)
The length of the Portuguese coast, the severity of the sea conditions and the concentration of population and economic activities on its coastal zone justify the importance of studying wave-induced risks and, in particular, flooding due to wave action. Indeed, emergency situations caused by adverse sea conditions are frequent and put in danger the safety of people and goods, with negative impacts for society, economy and natural heritage. So, assessing the risk of flooding of coastal and port areas is essential for the proper planning and management of these areas. In this framework, a methodology for the flood risk assessment in coastal and port areas is under development. The methodology is embedded into the HIDRALERTA system, a novel integrated system for port and coastal management, designed to prevent emergency situations, to support their management and to forecast incidental long-term interventions. The present paper describes the methodology, the HIDRALERTA system and a case study, the São João da Caparica beach, on the Lisbon’s area, where the referred methodology was recently applied. Sea wave characterization and flood level calculations are presented for the study.